Investigate The Factors of Community Intermittency Education in Remote Area (Case Study of Pujananting) - Nismawati,; Syamsu Andi Kamaruddin,; M. Ridwan Said Ahmad, (Technium Social Sciences Journal, 2024)
Intermittency Education is a phenomenon that is common in remote areas. This research aims to explore the factors that cause intermittency education in remote areas in Indonesia, namely Pujananting. This research uses a qualitative approach. Informants who were used as research subjects included local governments, teachers and communities experiencing intermittency education. Analysis in exploring the factors that cause intermittency education uses qualitative analysis. The results of the research show that the causes of intermittency education in communities in remote areas such as those in the Pujananting area consist of socio-economic conditions, social interactions, accessibility, and the role of the social environment. These causal factors are related to each other so that there needs to be continuous efforts to minimize the occurrence of intermittency education in the future.